2020
DOI: 10.1111/1467-9817.12341
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic learning and transfer of complex words: insights from eye tracking during reading and learning tasks

Abstract: Background: Efficient word identification is directly tied to strong mental representations of words, which include spellings, meanings and pronunciations. Orthographic learning is the process by which spellings for individual words are acquired. Methods: In the present study, we combined the classic self-teaching paradigm with eye tracking to detail the process by which complex pseudowords are learned. With this methodology, we explored the visual processing and learning of complex pseudowords, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…First, we observed significant correlations in type-1 performance in the experimental tasks related to orthographic lexical processing (VA span and orthographic lexical decision), both across tasks and with participants' performance in the standardized tests measuring word and pseudoword reading ability. This result is in line with previous research linking performance in the VA span task, with participants' level of orthographic knowledge reflected by the lexical decision task, and reading fluency measured by the standardized reading tests (Ginestet et al, 2021;Valdois et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, we observed significant correlations in type-1 performance in the experimental tasks related to orthographic lexical processing (VA span and orthographic lexical decision), both across tasks and with participants' performance in the standardized tests measuring word and pseudoword reading ability. This result is in line with previous research linking performance in the VA span task, with participants' level of orthographic knowledge reflected by the lexical decision task, and reading fluency measured by the standardized reading tests (Ginestet et al, 2021;Valdois et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Second, correlation analyses were run between type-2 metacognitive efficiency across the experimental tasks, and participants' scores on the standardized reading tests. We expected (i) participants with higher type-1 task sensitivity in the linguistic experimental tasks to exhibit higher performance across these tasks and on the standardized reading tests (e.g., (Ginestet et al, 2021;Valdois et al, 2019)) and (ii) participants with higher type-2 metacognitive efficiency to exhibit better performance across all our reading tasks.…”
Section: Correlations Between Type-1 Task Sensitivity and Type-2 Metacognitive Efficiency In The Experimental Tasks And Students' Performmentioning
confidence: 99%
“…First, we performed a verification check analysis regarding the relationship between inter-individual differences in type-1 performance on the experimental tasks and participants' general reading level assessed by the standardised reading tasks. Based on previous literature, it was a priori expected that performance on the experimental tasks assessing skills related to orthographic processing would correlate between them and with students' general reading level (e.g., Ginestet et al, 2021;Valdois et al, 2019). No association was expected between those and performance in the non-linguistic emotion recognition task.…”
Section: No Evidence For An Association Between Metacognitive Efficie...mentioning
confidence: 99%
“…Their findings demonstrate how the suffix plays an important role in mapping form and meaning in support of word learning. Ginestet et al (2021) illustrated the influence of morphological information at several different levels during adult word learning, supplementing an orthographic learning paradigm with eye movement recording. Eye movements during reading in the learning phase suggested that not only did morphological structure facilitate initial visual processing, it also seemed to result in more learningaccuracy on both spelling and orthographic choice tasks was higher for morphologically complex pseudowords than for matched monomorphemic pseudowords.…”
Section: Levels Of Processingmentioning
confidence: 99%
“…One of the goals of this special issue was to bring together empirical evidence from different languages and contexts to inform these questions. To this end, this special issue includes studies in Chinese (Cantonese; Qiao et al, 2021), French (Rassel et al, 2021), German (Fleischhauer et al, 2021;Görgen, De Simone, Schulte-Körne, & Moll, 2021) and Norwegian (Lyster et al, 2021) and studies in English that draw upon the varied educational contexts of the United Kingdom (Dawson et al, 2021;James et al, 2021), the United States (Goodwin et al, 2021) and Canada (Georgiou et al, 2021;Ginestet et al, 2021). Qiao et al (2021) explored the relationship between morphological awareness and reading comprehension in both Chinese and English with Chinese-English bilingual children in Hong Kong (8 to 10 years old).…”
Section: Cross-language Considerationsmentioning
confidence: 99%